(untitled) (KULT_online, 2021)
The volume Ukraine Verstehen: Auf den Spuren von Terror und Gewalt, published by the Centre for Liberal Modernity, is devoted to the investigation of the history of terror and violence in Ukraine in the 20th century. Over 20 experts articulate the complex memory about crimes of the Nazi and Soviet regimes committed on the territory of Ukraine and thematize the role of Memory Studies and Memory Politics in post-Soviet countries. The volume also illustrates how traumatic legacies are interrelated with the current situation in Ukraine.